Estimativa dos estoques de biomassa e nutrientes em florestas secundárias na Amazônia central - Pinto, Fabiana Rocha (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
This work evaluates the contents, storage and the distribution of nutrients in different parts of trees (leaves, fine and coarse branches, trunks, and fine and coarse roots), from two secondary forests with different history of uses and ages. Also the soil characterization of the two areas was conducted. Allometric equations were applyed to develop a model of the nutrient storage distribuion. The research was conducted in two areas northern of Manaus (AM, Brazil), at the EEST-Station: 1) ZF-2, where the primary forest was cutted in 1981 an abandoned one year later, and 2) S-8, where a ten year old secondary forest was cutted in 1991 and burned and abandoned in the same year. The variations of the mean nutrient contents in the tree parts of the two areas (ZF-2 e S-8) were: C dag kg-1 38 (coarse roots) - 52 (leaves and fine branches); Ng kg-1 - 3,0 (trunk) and 20,5 (leaves); P g kg-1 - 0,1 (fine roots and trunk) and 0,8 (leaves); K g kg-1 - 1,0 (trunk) and 6,7 (leaves); Ca g kg-1 - 1,0 (coarse branches) and 15,8 (bark trunk); Mg g kg-1 - 0,4 (coarse branches) and 2,5 (leaves); Mn mg kg-1 - 21 (coarse roots) and 185 (leaves); Fe mg kg-1 - 17 (coarse roots) and 400 (fine roots); Cu mg kg-1 - 2,6 (coarse roots) and 9,2 (leaves); Na mg kg-1 - 160 (coarse roots) and 1000 (bark coarse roots); Zn mg kg-1 - 6,0 (coarse roots) and 36 (bark coarse roots). Most content was found in the leaves, for two areas. The statistical differences (p<0,05) of the stocks and contents were statistic significant for all nutrients and tree parts The statistical analysis showed a similarity between the individual of the two areas. Nine models were tested in order to estimate the nutrient stocks in the individual trees, using the total biomass and the nutrient content of each tree part. The objective was to find the most adequate and representative model for the Manaus region. This model was a non-linear, using only the BHD (Pnut = β0 Di β1), with better results for Fe (R2 0,95; Syx % 5,89) and C (R2 0,91; Syx % 8,10). The soils of the three areas (two secondary and one primary forest) presented significant differences (p<0,05) only for K, Mn e Fe. However the higher values were observed in the superficial layer (0-2,5 cm), just the Fe, presented significant differences (p>0,05), due to the presence of the litter layer and the disponibilty of organic matter.